Manajemen Risiko Keuangan Dalam Menghadapi Ketidakpastian Ekonomi Global - Kevin (CV. SINAR HOWUHOWU, 2025)
This study examines financial risk management as a crucial strategy for navigating global economic uncertainty. Through a systematic review of relevant literature, case studies, and publications, it analyzes the evolution of risk management from a narrow, model-oriented quantitative approach to a holistic Enterprise Risk Management (ERM) framework. The findings indicate that historical financial crises have shifted the focus towards the integration of market, credit, and liquidity risks, as well as the need to manage operational and strategic risks. The research also reveals that strong corporate governance, a healthy risk culture, and the adoption of financial technologies (such as AI and big data) are key determinants in building financial resilience. This article concludes that effective risk management is an adaptive and dynamic process, enabling companies not only to survive market volatility but also to identify opportunities for creating long-term value.